Multiserver queueing networks and the tandem queue model. (1998) - Gall, Pierre Le
Abstract : Using a tandem queue model we evaluate the local endogenous (= internal) queueing delay in single server and multiserver queueing networks. The new concept of the apparent overall upstream queueing delay(as perceived by the downstream network) allows us to analyze the distribution of this local queue by interpolating between the distributions of the tandem queue (generated by a concentration tree ) and the isolated G / G / s queue . The interpolation coefficients depend on the proportion of premature departures , typically interfering in the upstream stage and leaving the considered path without being offered to the considered local queue. On the other hand, local exogenous arrivals (from outside the network) require the introduction of the interference delay concept. Finally, in the case of single server queueing networks, we stress the need to extend the capacities of the buffers, by considering the worst case scenario and by using an equivalent tandem queue model.